Exogenous Model Merging by means of Model Management Operators - Boronat, Artur (Electronic Communications of the EASST, 2007)
In Model-Driven Engineering, model merging plays a relevant role inthe maintenance and evolution of model-based software. Depending onthe amount of metamodels involved in a model merging process, we canclassify model merging techniques in two categories: endogenousmerging, when all the models to be merged conform to the samemetamodel; and exogenous merging, when the models to be mergedconform to different metamodels. MOMENT (MOdel manageMENT) is aframework that is integrated in the Eclipse platform, and provides acollection of generic set-oriented operators to manipulate MOFmodels, following the Model Management discipline. In this paper, westudy how model transformations are useful in a model mergingprocess and we provide a solution for both kinds of model merging bymeans of model management operators and the QVT Relations language.